Development of films based on chitosan, gelatin and collagen extracted from bocachico scales (Prochilodus magdalenae) (2024)
Biodegradable biopolymers from species of the animal kingdom or their byproducts are sus tainable as ecological materials due to their abundant supply and compatibility with the envi ronment. The research aims to obtain a biodegradable active material from chitosan, gelatin, and collagen from bocachico scales (Prochilodus magdalenae). Regarding the methodology, films were developed from gelatin, chitosan, and collagen from bocachico scales (Prochilodus mag dalenae) at different concentrations using glycerol as a plasticizer and citric acid as a cross-linker. The films were obtained with the hydrated mass processed by compression molding and char acterized according to humidity, water solubility, contact angle, mechanical properties, and structural properties. The results of the films showed a hydrophobic characteristic. First, the chitosan-collagen (CS/CO) films showed a yellowish color, while the gelatin-collagen (Gel/CO) films were transparent and less soluble than the gelatin-collagen (Gel/CO) films. Concerning mechanical properties, gelatin films showed higher stiffness and tensile strength than chitosan films. Furthermore, in the morphological analysis, more homogeneous chitosan films were ob tained by increasing the concentration of citric acid. In general, chitosan, gelatin, and collagen extracted from the scales of the bocachico (Prochilodus magdalenae) are an alternative in the application of films in the food industry.